Analisis Pengaruh PMDN, PMA, dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Provinsi Tahun 2005-2023 - Basri, Muh Nur Risky; Astuti, Sri; Jamil, Muh; Irwandi, Irwandi; Rajab, Abdul (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze whether there is an effect of domestic investment (PMDN), foreign investment (PMA), and labor on economic growth in South Sulawesi Province. This research used a type of quantitative research with multiple linear regression analysis methods with the help of Eviews 12 software. The location of this research is in South Sulawesi Province with secondary data collected periodically (times series) obtained from the South Sulawesi Provincial Statistics Agency and the South Sulawesi Provincial Investment and One-Stop Service Office. The period in this study is 19 years in the span of 2005-2023. The results of this study indicate that Domestic Investment has no effect, while Foreign Investment and Labor have a significant effect on Economic Growth in South Sulawesi Province.